INVESTIGATING THE PLEASURE READING HABIT OF THE STUDENTS OF UNIVERSITY OF ISLAM MALANG DURING THE COVID-19 PANDEMIC - Rara Dwi Ayuningtyas (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This research aimed at investigating the students’ pleasure reading habit during pandemic since they spend most of their time at home including their school activities done at home. This research used qualitative descriptive method. There were 25 students of 8th semester of English education Department of University of Islam Malang as the subjects of this study. The data were collected using questionnaire and interview. The findings showed that the students' reading habits during this pandemic continued but with a different frequency than before the pandemic. Then, the students revealed that their duration of using devices, especially mobile phones increased because they spent most of their time at home during the pandemic. All students said that they used their mobile phones more often to read because it was more practical. Next, from the data collected, it could be concluded that the main factor that hindered students from reading during the pandemic was social media.Keywords: Reading Habit, Pleasure reading, Factor influencing reading habit